2015
DOI: 10.1186/s13613-015-0093-5
|View full text |Cite
|
Sign up to set email alerts
|

Renal replacement therapy in adult and pediatric intensive care

Abstract: Acute renal failure (ARF) in critically ill patients is currently very frequent and requires renal replacement therapy (RRT) in many patients. During the last 15 years, several studies have considered important issues regarding the use of RRT in ARF, like the time to initiate the therapy, the dialysis dose, the types of catheter, the choice of technique, and anticoagulation. However, despite an abundant literature, conflicting results do not provide evidence on RRT implementation. We present herein recommendat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 171 publications
(162 reference statements)
5
40
0
Order By: Relevance
“…Recently, a prospective observational study demonstrated that ICU acquired infections in patients with sepsis contributed modestly to overall mortality21. Additionally, a retrospective study illustrated that early deaths were mainly attributable to intractable multiple organ failure, while secondary infection was the second leading cause of late death among patients with severe sepsis and septic shock11. Similarly, in present study, we found that the risk of late death for septic shock patients with secondary infection was about 5.8 times higher than that for patients who remained free of secondary infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a prospective observational study demonstrated that ICU acquired infections in patients with sepsis contributed modestly to overall mortality21. Additionally, a retrospective study illustrated that early deaths were mainly attributable to intractable multiple organ failure, while secondary infection was the second leading cause of late death among patients with severe sepsis and septic shock11. Similarly, in present study, we found that the risk of late death for septic shock patients with secondary infection was about 5.8 times higher than that for patients who remained free of secondary infection.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that the rates of common opportunistic bacteria and fungi increased significantly in the late phase (>15 days) of severe sepsis and septic shock when compared with the early phase (<6 days) of the disease. Further, another retrospective study found that septic shock patients who died more than 3 days after intensive care unit (ICU) admission were related to ICU-acquired complications, including secondary infections11. In contrast, evidence provided by Goldenberg et al .…”
mentioning
confidence: 99%
“…Unfractionated heparin - due to its pharmacokinetics and reversibility - has been widely used for CRRT ACG for decades [14]. According to the literature, heparin is an effective ACG in CRRT therapy with a mean dose of 11.1-20 U/kg/h and a post-filter ACT being maintained between 180 and 240 sec.…”
Section: Discussionmentioning
confidence: 99%
“…Dual lumen catheters between 7 F and 13 F were individually adapted to the child’s morphology and body weight according to literature recommendations, using the same criteria for patients treated with citrate (RCA) and heparin anticoagulation (Hep-ACG) [11, 14]. Hollow-fiber filters were used depending on the body weight of the patient according to the manufacturer’s guidelines [15].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, irrespective of the type of admission (medical, surgical, or trauma) and after adjustment for important confounders (illness severity and comorbidities), the need to acutely administer a high volume of fluid or a positive fluid balance over time is independently and reproducibly associated with more ICU complications (including AKI [11, 12]) and higher mortality [13], especially in patients with underlying kidney or heart disease [14]. In addition, many questions remain unsolved.…”
mentioning
confidence: 99%